Spatial Analysis of Fish Diversity, Evenness, and Dominance During the Seasonal Transition Period for Ecosystem Health Assessment - Ainy, Noer Sarifah; Sjahfirdi, Luthfiralda; Patria, Mufti Petala; Harinaldi, Harinaldi; Mujadid, Iqbal (Journal Of Biology Education Research (JBER), 2026)
Freshwater ecosystems, particularly small lakes, play a crucial role in maintaining biodiversity and supporting essential ecological functions, yet they are highly vulnerable to environmental disturbances. Small lakes are increasingly exposed to anthropogenic pressures such as land use change, nutrient enrichment, and declining water quality, making biological assessment essential for detecting ecosystem degradation. This study aimed to identify segment level patterns of fish diversity, evenness, and dominance during the seasonal transition period and to determine whether these patterns can distinguish relatively balanced ecological zones from priority stress zones for ecosystem management. An ecologically based quantitative descriptive approach was applied using spatial zoning of inlet, middle, and outlet segments. Fish assemblages were assessed using the Shannon–Wiener diversity index (H′), Evenness (E), and Simpson’s dominance index (D). The results revealed clear spatial variation in community structure among sampling segments. Some systems exhibited strong internal ecological gradients characterized by decreasing diversity and increasing dominance toward downstream segments, whereas others showed more transitional or relatively uniform patterns. Community composition analysis indicated assemblage compression and potential biotic homogenization driven by a limited number of dominant taxa. Exploratory analyses further suggested that higher alkalinity, hardness, and chlorine levels were associated with lower diversity and greater dominance. These findings demonstrate that fish community indices provide effective biological indicators of ecosystem condition and can support spatially targeted monitoring, conservation, and management of small freshwater ecosystems. The study also highlights the importance of incorporating spatially explicit community assessments into ecosystem health evaluation frameworks.